Simulations and Solutions of Calculus Problem: An Effort to Improve Students' Innovative and Quality Computing Skills - Sucipto, Lalu; Irpan, Samsul (Universitas Muhammadiyah Mataram, 2022)
One of the impacts of online learning that is not optimal is learning loss. Therefore, the aims of this study, we conduct computing practicum with Maple and Matlab to improve students' ability to develop learning media based on Network Virtual Laboratory (NVL). The implications of this practicum can improve students' innovative attitudes in developing various learning media NVL-based, with still through the validation process and field tests so that quality learning media is produced . The subject of this study consisted of 61 students who took the integrated mathematics computing course calculus . This is a development research (R&D), where each student develops learning media then validated and field trials. We assess each media resulting from the development using questionnaires and field observations. The results showed that as many as 85% of students have been able to innovate well in developing learning media NVL-based including function limit materials, derivatives, and integrals. The results of the assessment of the expert team showed that the ability of students in developing learning media reached an average score of 3.97 which is categorized as